TINJAUAN HUKUM ISLAM TERHADAP PENYELESAIAN KREDIT MACET PADA PEMBIAYAAN MURABAHAH DI KBMT (KOPERASI BAITUL MAAL WAT TAMWIL) AL-MUAWANAH - Zainul Abidin, Muhamad (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2024)
The objectives of this study are: To find out how the settlement of bad credit murabahah financing at the Baitul Maal Wat Tamwil Al-Muawanah Cooperative and other options used to resolve it; and to find out how Islamic law reviews the settlement of bad credit murabahah financing at the Baitul Maal Wat Tamwil Al Muawanah Cooperative. The basis of this research with the type of data used is qualitative data. The research used is included in the category of field research, which is descriptive analysis, namely where it describes and describes the circumstances and and phenomena that are clearer about the situation that occurs in an institution. The results of this study indicate that: Bad credit financing on murabahah financing is caused by two factors, namely external factors and internal factors. There are several alternative solutions including reschedulling. The legal review in handling problematic financing is found in Surah Al-Baqoroh verse 280, namely by giving deferred to customers. And in accordance with the settlement made by the Baitul Maal Wat Tamwil Al-Muawanah Cooperative